2009
DOI: 10.1187/cbe.09-02-0012
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory-intensive Course on RNA Interference and Model Organisms

Abstract: RNA interference (RNAi) is a powerful method to silence gene expression in a variety of organisms and is generating interest not only as a useful tool for research scientists but also as a novel class of therapeutics in clinical trials. Here, we report that undergraduate and graduate students with a basic molecular biology background were able to demonstrate conceptual knowledge and technical skills for using RNAi as a research tool upon completion of an intensive 8-wk RNAi course with a 2-h lecture and 5-h la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Moreover, 18 of the 20 students from the two combined classes were graduate students who are expected to have a better basic understanding of the importance of these interactions and experience reading and presenting primary literature. This trend mirrors the results observed in the assessment of a previous course taught within the Biotechnology Program [17].…”
Section: Course Outcomessupporting
confidence: 82%
“…Moreover, 18 of the 20 students from the two combined classes were graduate students who are expected to have a better basic understanding of the importance of these interactions and experience reading and presenting primary literature. This trend mirrors the results observed in the assessment of a previous course taught within the Biotechnology Program [17].…”
Section: Course Outcomessupporting
confidence: 82%
“…The discovery of RNAi resulted in a Nobel Prize and has enabled the insertion of exogenous double-stranded RNA to trigger RNAi and knock down gene expression without altering the DNA sequence (13). Similarly, there has been an increasing emphasis in teaching RNAi, including incorporating RNAi into lab courses (46). However, there remains a paucity of lecture-based activities to teach about RNAi.…”
Section: Introductionmentioning
confidence: 99%
“…However, practical considerations, including funding and time constraints often make it difficult to achieve that goal. Accordingly, many examples of laboratory courses that engage groups of students in discovery‐based research related to ongoing faculty research have been reported .…”
Section: Introductionmentioning
confidence: 99%